2020
DOI: 10.1108/ijshe-11-2019-0338
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the environmental behavior of business and accounting university students

Abstract: Purpose The purpose of this study is to explore the underlying dimensions of environmental behavior (EB) and examine how environmental education (EE) and ecological sensitivity (ES) motivate the EB of Business Administration and Accounting students (BAS). Design/methodology/approach A questionnaire survey was conducted and a sample of 190 BAS was randomly selected from the departments of Business Administration and Accounting and Finance at the University of West Attica (UNIWA), Greece. Findings The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
1
22
1
2
Order By: Relevance
“…This study examined the direct influence of environmental commitment, environmental consciousness, green lifestyle, and green self-efficacy on pro-environmental behaviour. It should be highlighted that after a review of the most significant and recent works students' pro-environmental behaviour, such as [22,[25][26][27][28][29][30][31][32][33][34][35][36], no similar research was found. In addition, previous empirical studies on pro-environmental behaviour have been conducted in relation to environmental commitment [37][38][39], environmental consciousness [40,41], lifestyle practices [42], green lifestyle [5,43], and self-efficacy [13,[44][45][46][47].…”
Section: Need For the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This study examined the direct influence of environmental commitment, environmental consciousness, green lifestyle, and green self-efficacy on pro-environmental behaviour. It should be highlighted that after a review of the most significant and recent works students' pro-environmental behaviour, such as [22,[25][26][27][28][29][30][31][32][33][34][35][36], no similar research was found. In addition, previous empirical studies on pro-environmental behaviour have been conducted in relation to environmental commitment [37][38][39], environmental consciousness [40,41], lifestyle practices [42], green lifestyle [5,43], and self-efficacy [13,[44][45][46][47].…”
Section: Need For the Studymentioning
confidence: 99%
“…The existing literature on pro-environmental behaviour is largely influenced by perspectives from developed countries [19,23,26,27,32], while existing works from developing countries [31] generally do not discuss the topic in the Malaysian context.…”
mentioning
confidence: 99%
“…Many studies discuss the issue of awareness, as well as educating and training students, for a sustainable society by creating an adequate curriculum [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Επιπλέον, υπάρχουν έρευνες οι οποίες έχουν χρησιμοποιήσει την κλίμακα είτε σε κάποια μικρότερη έκδοσή της, δηλαδή με λιγότερες δηλώσεις ή ομάδες δηλώσεων (Bjerke et al, 2006;Grebitus et al, 2013), είτε τροποποίησαν δηλώσεις ή ομάδες δηλώσεων (Kyriakopoulos et al, 2020;Li et al, 2020 (Bernstein & Szuster, 2019). Επιπλέον, με την κατάλληλη χρήση ποσοτικών κλιμάκων μέτρησης, μπορεί να υπάρχουν ορθότερα αποτελέσματα στο φιλοπεριβαλλοντισμό (Bernstein & Szuster, 2019).…”
Section: η διασφάλιση της ποιότητας στην εκπαίδευσηunclassified
“…Η τροποποίηση και προσαρμογή του μοντέλου του Dunlap, ως προς τις ομάδες, τις όψεις και το περιεχόμενο των δηλώσεων του εργαλείου της παρούσας έρευνας, συμφωνεί με πολλές έρευνες όσον αφορά το μέγεθος (Bjerke et al, 2006;Grebitus et al, 2013) και το περιεχόμενο (Kyriakopoulos et al, 2020;Li et al, 2020) και διαφωνεί με άλλες (Cleveland et al, 2016;Cotton et al, 2021;Du et al, 2019;Wardropper et al, 2020 (Riya, 2018) και στις διατροφικές προτιμήσεις (Hoflund et al, 2019). Οι όψεις της ομάδας της διατροφής στην παρούσα έρευνα, συμφωνεί με έρευνες που εξετάζουν το θέμα των ψυχογραφικών χαρακτηριστικών, με τις γνώσεις, στάσεις και συμπεριφορές απέναντι στα τρόφιμα (Aitsidou et al, 2019;Hansen et al, 2018;Laureti & Benedetti, 2018b;Steiner et al, 2017;Yazdanpanah et al, 2015 (Finnell & John, 2017;Mamat & Mokhtar, 2012;Pitman et al, 2018bRodríguez-Ortega et al, 2016aSteiner et al, 2017;Stylidis et al, 2018;Tabi et al, 2014;Weaver, 2012), αλλά και με τη θεωρία του Dunlap στην οποία βασίζεται το προτεινόμενο εργαλείο.…”
Section: τμηματοποίηση των επισκεπτών του αγροκτήματος σύμφωνα με τους κύριους δείκτες ποιότηταςunclassified